Case Study on Using Mundu-Paciran Nannofossil Zones (MPNZ) to Subdivide Mundu and Paciran Sequences in the MDA Field, East Java Basin, Indonesia - Azhali Edwin; Kian Han; Wildanto Nusantara (Berita Sedimentologi, 2013)
The Husky-CNOOC Madura Limited (HCML) MDA-4 exploration well (2011) in the Madura Strait region targeted Globigerina limestones in the Mundu Sequence (3.8 Ma) and the Paciran Sequence (2.0 Ma). The MDA Field is covered by Merpati 3D Seismic (2005). Seismic features observed from the 3D volume include phase change or polarity reversal at the top of gas filled reservoirs of the MDA structure and DHI flat-spot approximating to the gas-water contact (GWC). The reservoirs are primarily planktonic foraminifera grainstones, packstones and wackestones that have been deposited as pelagic rains and were subsequently redistributed by sea floor bottom currents.Differentiating the Mundu and Paciran Sequences relies heavily on biostratigraphy and chronostratigraphy, as there are no significant lithological features that can be observed between the sequences. This article introduces a method to construct detailed well correlations of the two sequences based on Mundu–Paciran Nannofossil Zones (MPNZ), using high resolution biostratigraphy events. The methodology uses varying nannofossil abundances in the interval NN18 (Late Pliocene) to NN11 (Late Miocene). The best reservoir performance in the study area may occur in the MPNZ-7 and MPNZ-6, which were deposited at the late stage of the depositional cycles.